Drought tolerance of local dryland rice varieties from the far western Santa Catarina, Brazil (Research, Society and Development, 2021)
Drought is the main factor of abiotic stress in dryland rice cultivation, responsible for considerable productivity losses and grain quality damages, as well as genetic erosion of local varieties of this crop. The use of indices in the drought tolerance estimation in grains of this crop is acquiring importance for its advantages in the operationalization of tests of comparison between genotypes and their effectiveness in the differentiation of responses to drought stress. Among local dryland varieties of rice preserved by small-scale farmers in far western Santa Catarina, different responses to drought tolerance are expected. The identification of these differential responses is important in the context of agrobiodiversity conservation, genetic improvement, and as an alternative to the effects of climate changes. The objective of the present study was to evaluate thirty-four local varieties of dryland rice from far western Santa Catarina regarding drought tolerance. For this aim, this work used the DTD (Drought Tolerance Degree) methodology. Fifteen varieties showed greater resistance when submitted to a water restriction level of 10% in water moisture. On the other hand, six varieties were more resistant to moderate stress (20%). Finally, three varieties were among the most resistant in the two applied stress levels.